Calculus

posted by .

find the derivatives of the given functions.
g(t)=sqrt t(1+t)/t^2
the sqrt is just over t.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math calculus please help!

    l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ?
  2. Inequality

    When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution?
  3. Math

    How do you find a square root of a number that's not a perfect square?
  4. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  5. Calculus

    Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
  6. Math/Calculus

    Solve the initial-value problem. Am I using the wrong value for beta here, 2sqrt(2) or am I making a mistake somewhere else?
  7. Calculus

    Find the outside and inside functions of the following to find their derivatives: 1) sqrt(2x+9) 2) cos(cos(x)) 3) tan(x) I already know how to find their derivatives I'm just not exactly sure what parts of the chain rule equation would …
  8. Calculus check

    Given f(x)=x^4(2x^2-15). On what interval(s) is the graph of f concave upwards?
  9. Calculus

    Find the equation of the tangent line to f(x)=x sec x at (pi/4, pi •sqrt of 2 all over 4). I got to here, but did not know what to do next: slope: (pi/4)(sqrt of 2 over 2) + (sqrt of 2 over 2) everything over 1/2=.......
  10. Calculus

    We just learned derivatives and now on the Chain Rule. y = r/[(sqrt)(r(sqrd)+1)] y' = [[(sqrt)(r(sqrd)+1)(r)'] - [(r)(sqrt)(r(sqrd)+1)']] / [(sqrt)(r(sqrd)+1)](sqrd) y' = (sqrt)(r(sqrd)+1) - r[1/2(r(sqrd)+1)(raised to -1/2)](2r) My …

More Similar Questions